1991
DOI: 10.1017/s0950268800048366
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group, secretor status and detection ofHelicobacter pyloriamong patients with gastric or duodenal ulcers

Abstract: SUMMARYPatients (454) referred for gastroscopy to the General Hospital of Athens were examined to determine (1) if non-secretors were over-represented among patients with ulcers and (2) is there was an association with ABO blood group or secretor status and carriage of Helicobacter pylorn.Compared with the local population, among patients with either gastric ulcer (51) or duodenal ulcer (96) there was a significant increase in the proportion of those who were blood group 0 (P < 0 025); however, there were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 32 publications
5
56
4
Order By: Relevance
“…The distribution of the ABO blood group phenotypes did not differ between the two camps and were similar to those we found in a previous study [16] and that reported by Hirzfeld and Hirzfeld in 1919 [17]. Several of the factors examined in the study varied between the two camps.…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of the ABO blood group phenotypes did not differ between the two camps and were similar to those we found in a previous study [16] and that reported by Hirzfeld and Hirzfeld in 1919 [17]. Several of the factors examined in the study varied between the two camps.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with blood group O were found to be more susceptible to peptic ulcer disease for decades without known cause until the relationship between Lewis b antigens and the attachment of H. pylori to gastric mucosa was observed (11)(12)(13). However, the correlation between H. pylori infection and ABO blood types was not supported in some reports (14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…People with blood group O have been noted to be more susceptible to peptic ulcer disease for decades without appropriate explanations (11). In 1993, Boren et al (12) reported that people with blood group O had more H. pylori receptors, and Lewis b antigens mediated the attachment of H. pylori to the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The nonsecretor status of this individual is interesting in view of the increased prevalence of duodenal ulcer among non-secretors (47)(48)(49). One study (50) has demonstrated that non-secretion is not associated with increased susceptibility to infection with H. pylori.…”
Section: Discussionmentioning
confidence: 99%